MESENCHYMAL STEM CELLS OF ADIPOSE TISSUE: A MODERN VIEW, THE RELEVANCE AND PROSPECTS OF APPLICATION IN PLASTIC SURGERY - O. I. Startseva; D. V. Melnikov; A. S. Zakharenko; K. A. Kirillova; S. I. Ivanov; E. D. Pischikova; G. E. Dashtoyan (Исследования и практика в медицине)
Nowadays autotransplantation of adipose tissue is the most popular subject for research in the field of plastic surgery and regenerative medicine. Transplantation of adipose tissue is widely recognized as a common technique to increase the volume of soft tissues or for filling of soft tissue defects caused by trauma or the aging process. Injections of autologous fat are widely used in plastic surgery and regenerative medicine, as performed transplant sometimes gives unpredictable and too short due to partial necrosis or progressive resorption of fat (from 20 to 60% according to various authors). Many scientists who involved in plastic surgery around the world (USA, Europe, China, Japan) has revised its Outlook on the problem of transplantation of own fat tissue in connection with the advances in cellular technologies. Currently, the main object of study in this area are growth factors, which can affect the degree of engraftment of the adipose tissue and make it more predictable. This literature review describes the experimental studies focused on the study of the angiogenic properties of SCAT (stem cells of adipose tissue) and SVCF (stromal- vascular cell fraction) and their use for the stimulation of neovascularization and improving the survival of fat grafts in plastic surgery and regenerative medicine. The results of studies on the survival of fat autografts in animal and clinical studies with the combination of dif ferent methods that improve the vascularization of adipose tiss ue.